APPLYING A GENERAL STRAIN THEORY FRAMEWORK TO UNDERSTAND SCHOOL WEAPON CARRYING AMONG LGBQ AND HETEROSEXUAL YOUTH1. Issue 4 (25th September 2017) - BUTTON, DEEANNA M.; WORTHEN, MEREDITH G. F.
Abstract: Lesbian, gay, bisexual, and questioning (LGBQ) youth are at a higher risk for school victimization, social isolation, and school weapon carrying compared with their heterosexual peers, yet few studies have been conducted to investigate their experiences. By using a general strain theory (GST) framework, data from the Youth Risk Behavior Survey (YRBS) statewide probability sample of Delaware heterosexual (n = 7, 688) and LGBQ (n = 484) youth in grades 9–12 show that there are both similarities and differences in the factors associated with school weapon carrying among LGBQ and heterosexual youth. LGBQ and heterosexual youth's weapon carrying is related to school victimization, but social support does not moderate the relationship between school victimization and school weapon carrying as suggested by GST. Furthermore, being male is significantly related to heterosexual youth's weapon carrying, but sex is not related to weapon carrying among LGBQ youth. Overall, the results highlight a need to reconceptualize GST to help center the experiences of LGBQ youth, a historically marginalized group, within mainstream criminological literature. Theoretical and policy implications are discussed.